Comparison of compact toroid configurations - Bellan, P.M.; Dolan, T.J. (Вопросы атомной науки и техники, 2000)
The IAEA Coordinated Research Project (CRP) on "Comparison of Compact Toroid Configurations" has participants from Argentina, Brazil, China, India, Israel, Italy, Japan, Russia, Ukraine (Dr. Yaroslav Kolesnichenko), UK, and USA. The results of a recent CRP meeting are summarized here. Spherical tokamaks (ST) have very low aspect ratios, which facilitates attainment of high b. Spheromaks have both poloidal and toroidal fields, but no center post. Field reversed configurations (FRC), have only poloidal magnetic fields.